Studi Kasus: Penerapan Terapi SI-VIGUR (Virtual Reality Guided Imagery) Terhadap Nyeri Kronis pada Lansia dengan Rheumatoid Arthritis di Panti Jompo - Pastari, Marta; Martini, Sri; Farama, Dodi Aflika; Somad, Abdul; Detiana, Detiana; Haryanti, Eka; Wibowo, Wahyu Dwi Ari (Universitas Malahayati, 2025)
ABSTRACT Chronic pain in older adults with Rheumatoid Arthritis (RA) is a significant health problem, often leading to impairments in daily activities, anxiety, and a decreased quality of life. This condition necessitates accessible and effective non-pharmacological interventions to address pain in the older adult population. This case study aims to implement and analyze the results of applying Virtual Reality Guided Imagery (SI-VIGUR) therapy as a nursing intervention to reduce chronic pain in older adult patients with Rheumatoid Arthritis at Tresna Werda Nursing Home, Lubuklinggau City in 2025. This case study involved two older adult individuals (Ny. S and Ny. A) suffering from Rheumatoid Arthritis with complaints of chronic pain. The SI-VIGUR intervention was implemented for 3 consecutive days for each subject. Evaluation was conducted daily using pain level indicators from SLKI (Standard for Nursing Outcome Indicators, Indonesia) on a 1-5 scale (Increased to Improved), which included Protective Behavior, Pain Complaints, and Restlessness, as well as the Numeric Pain Scale (0-10). The implementation of SI-VIGUR consistently showed significant improvement across all indicators of chronic pain in both subjects. For Ny. S, the pain scale decreased from 6 at the beginning of the intervention to 2 on the third day, accompanied by improvements in Protective Behavior, Pain Complaints, and Restlessness, which showed progress from 'Initial Assessment' values to 'Improved' at the end of the intervention. Ny. A also showed a similar pattern of improvement, with the pain scale decreasing from 6 to 3 on the third day, although it was stagnant on the second day, and SLKI indicators also showed improvement. Both subjects reported increased relaxation and improved sleep quality. The application of Virtual Reality Guided Imagery (SI-VIGUR) is an effective, easily applicable, and highly potent non-pharmacological nursing intervention for reducing chronic pain in older adult patients with Rheumatoid Arthritis. The success of this intervention highlights the role of technology in supporting complementary therapies to improve the quality of life of the older adults. Keywords: Chronic Pain, Older Adults, Rheumatoid Arthritis, Virtual Reality Guided Imagery (SI-VIGUR). ABSTRAK Nyeri kronis pada lansia dengan Rheumatoid Arthritis (RA) merupakan masalah kesehatan yang signifikan, seringkali menyebabkan gangguan aktivitas sehari-hari, kecemasan, dan penurunan kualitas hidup. Kondisi ini menuntut adanya intervensi non-farmakologis yang mudah diakses dan efektif untuk mengatasi nyeri pada populasi lansia. Studi kasus ini bertujuan untuk mengimplementasikan dan menganalisis hasil penerapan terapi Virtual Reality Guided Imagery (SI-VIGUR) sebagai intervensi keperawatan untuk mengurangi nyeri kronis pada pasien lansia dengan Rheumatoid Arthritisdi Panti Jompo Tresna Werda Kota Lubuklinggau pada tahun 2025. Studi kasus ini melibatkan dua individu lansia (Ny. S dan Ny. A) yang menderita Rheumatoid Arthritis dengan keluhan nyeri kronis. Intervensi SI-VIGUR diimplementasikan selama 3 hari berturut-turut pada masing-masing subjek. Evaluasi dilakukan harian menggunakan indikator tingkat nyeri dari SLKI dengan skala 1-5 (Meningkat hingga Membaik), yang mencakup Sikap Protektif, Keluhan Nyeri, dan Gelisah, serta Skala Nyeri Numerik (0-10). Implementasi SI-VIGUR secara konsisten menunjukkan perbaikan signifikan pada semua indikator nyeri kronis pada kedua subjek. Untuk Ny. S, skala nyeri menurun dari 6 pada awal intervensi menjadi 2 pada hari ketiga, disertai perbaikan pada Sikap Protektif, Keluhan Nyeri, dan Gelisah yang menunjukkan progres dari nilai 'Penilaian Awal' menjadi 'Membaik' pada akhir intervensi. Ny. A juga menunjukkan pola perbaikan serupa, dengan skala nyeri menurun dari 6 menjadi 3 pada hari ketiga, meskipun sempat stagnan di hari kedua, dan indikator SLKI juga menunjukkan perbaikan. Kedua subjek melaporkan peningkatan relaksasi dan kualitas tidur. Aplikasi Virtual Reality Guided Imagery (SI-VIGUR) merupakan intervensi keperawatan non-farmakologis yang efektif, mudah diterapkan, dan berpotensi besar untuk mengurangi nyeri kronis pada pasien lansia dengan Rheumatoid Arthritis. Keberhasilan intervensi ini menyoroti peran teknologi dalam mendukung terapi komplementer guna meningkatkan kualitas hidup lansia. Kata Kunci: Rheumatoid Arthritis, Nyeri Kronis, Lansia, Virtual Reality Guided Imagery (SI-VIGUR).